Enriched Catalytic Activity of TiO2 Nanoparticles Supported by Activated Carbon for Noxious Pollutant Elimination - Suriyaprabha Rajendran; Gajendra Kumar Inwati; Virendra Kumar Yadav; Nisha Choudhary; Mitesh B. Solanki; Magda H. Abdellattif; Krishna Kumar Yadav; Neha Gupta; Saiful Islam; Byong-Hun Jeon (Nanomaterials, 2021)
Cleaning wastewater has become one of the most serious issues for a number of scientists and researchers in recent years, as water is the most basic need for the daily life of humans. There has been a focus on the removal of noxious pollutants from wastewater effluents by using nanocatalysts owing to their unique physicochemical actions and stability. Herein we manufactured TiO2 nanoparticles supported by activated carbon (AC-TiO2) using a cost-effective sonochemical method. The band structures of the AC-TiO2 and TiO2 were modified from 3.2 to 3.1 eV, thus increasing the catalytic activity. The structural, optical and anatase crystal phase properties, with morphological confirmation, were studied by applying UV-DRS, PL, FESEM, XRD, along with HRTEM, respectively. The specific surface area, calculated by BET analysis, was found to be ~241 m2/gm and ~46 m2/gm for AC-TiO2 and TiO2. The degradation efficiency of the as-prepared nanocatalysts against the very toxic but rarely studied organic textile dye pollutant RO 84 was investigated and 97% efficiency were found for the AC-TiO2 as compared to pure TiO2, which is a highly appreciated finding in the catalytic dye degradation application domain. Such surface-modified nanocatalysts could be further implemented for the treatment of wastewaters/waste effluents released from chemical industries, laboratories and other sources.